A review on the erosion mechanisms in abrasive waterjet micromachining of brittle materials. (15th April 2019) - Nguyen, T; Wang, J
Abstract: The fabrication of miniature structures on components with high-integrity surface quality represents one of the cutting edge technologies in the 21st century. The materials used to construct such small structures are often difficult-to-machine. Many other readily available technologies either cannot realise necessary precision or are costly. Abrasive waterjet (AWJ) is a favourable technology for the machining of difficult-to-machine materials. However, this technology is generally aimed at large stock removal. A reduction in the scale of this technology is an attractive avenue for meeting the pressing need of industry in the production of damage-free micro features. This paper reviews some of the work that has been undertaken at UNSW Sydney about the development of such an AWJ technology, focusing on the system design currently employed to generate a micro abrasive jet, the erosion mechanisms associated with processing some typical brittle materials of both single- and two-phased. Processing models based on the findings are also presented. The review concludes on the viability of the technology and the prevailing trend in its development.